A regional haemovigilance retrospective study of four types of therapeutic plasma in a ten‐year survey period in France. Issue 4 (7th January 2013) - Bost, V.; Odent‐Malaure, H.; Chavarin, P.; Benamara, H.; Fabrigli, P.; Garraud, O.
<x xml:space="preserve">Abstract</x> Background and objectives Our objective was to compare the frequency of adverse events (AEs) due to any of the 4 types of fresh‐frozen plasma (FFP) prepared and delivered by the French Blood Establishment (EFS) over a 10‐year period. Surveillance of AEs and vigilance was performed according to a homogeneous policy. The four types of FFP comprised of one type (methylene blue [MB) that was stopped since then and of another type [amotosalen (AI)] that was recently introduced, along with two conventional products [quarantine (Q) and solvent–detergent (SD)]. Materials and Methods This is a retrospective study based on the national AE reporting database and on the regional database system for deliveries. AEs recorded after the delivery of 1 of the 4 types of FFP were pairwise compared, with appropriate statistical corrections. Results 105 964 FFP units were delivered (38·4% Q, 17·9% SD, 9·7% MB and 34% AI). Statistical comparisons of AEs identified only a difference in AE rates between quarantine and solvent–detergent plasma. Conclusions FFP was confirmed to be extremely safe in general, especially if one considers 'severe' AEs. All types of FFP were associated with extremely low occurrences of AEs. Q, SD, MB and AI led, respectively, to 7·14, 4·86, 1·05 and 4·16 AEs per 10 000 deliveries.